Inventory of clams (Tridacnidae) on Biang Island, Matak Village, Kute Siantan District, Anambas Islands Regency, Riau Islands, Indonesia - Pajrin Buhari; Susiana Susiana; Jumsurizal Jumsurizal (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
Research on the inventory of clams (Tridacnidae) at Biang Beach, Matak Village, Kute Siantan District, Anambas Islands Regency, clams have been included in the CITES list, appendix II. The purpose of this study was to determine the physico-chemical parameters in the Biang Coastal Waters, Kute Siantan District, and to determine the types of clams found in the Biang Coastal Waters, Matak Village, Kute Siantan District. Knowing the Density of Kima in Biang Beach Waters, Matak Village, Kute Siantan District, this research was conducted in March 2021, located in Matak Village, Anambas Islands Regency. sampling using purposive sampling method which consists of 6 points determination of the point based on the distribution of coral reefs as the survival of clams. sampling of clams (Tridacnidae) using Bhentos Belt Transect (BBT), the results of measuring water parameters are still at the threshold of the quality standard of PP RI No. 22 of 2021, The highest density was in the clam species Tridacna crocea with a density value of 714.29 ind/ha at point 6 (six), then the lowest density value was at point 3 (three) with a value of 142.86 ind/ha, The highest density was at Kima Tridacna maxima species with a density value of 1,285.71 ind/ha at point 6 (six) then the lowest density value was at point 5 (five) with a density value of 500.00 ind/ha, while the density value at the clam species Tridacna squamosa, with a value of 142.86 ind/ha, was found at point 6 (six) and the density value of the species Hippopus hippopus with a value of 71.43 ind/ha was at point 3 (three).